Treatment of Experimental Cerebral Malaria by Slow Release of Artemisone From Injectable Pasty Formulation - Golenser, Jacob; Salaymeh, Nadeen; Higazi, Abd Alroof; Alyan, Mohammed; Daif, Mahran; Dzikowski, Ron; Domb, Abraham J. (Frontiers in Pharmacology, 2020)
Malaria caused by Plasmodium falciparum causes numerous cases of morbidity with about 400,000 deaths yearly owing, mainly, to inflammation leading to cerebral malaria (CM). CM conventionally is treated by repetitive administration of anti-plasmodial drugs and supportive non-specific drugs, for about a week. A mouse model of CM caused by Plasmodium berghei ANKA, in which brain and systemic clinical pathologies occur followed by sudden death within about a week, was used to study the effect of artemisone, a relatively new artemisinin, within an injectable pasty polymer formulated for its controlled release. The parasites were exposed to the drug over several days at a non-toxic concentrations for the mice but high enough to affect the parasites. Artemisone was also tested in cultures of bacteria, cancer cells and P. falciparum to evaluate the specificity and suitability of these cells for examining the release of artemisone from its carrier. Cultures of P. falciparum were the most suitable. Artemisone released from subcutaneous injected poly(sebacic acid-ricinoleic acid) (PSARA) pasty polymer, reduced parasitemias in infected mice, prolonged survival and prevented death in most of the infected mice. Successful prophylactic treatment before infection proved that there was a slow release of the drug for about a week, which contrasts with the three hour half-life that occurs after injection of just the drug. Treatment with artemisone within the polymer, even at a late stage of the disease, helped to prevent or, at least, delay accompanying severe symptoms. In some cases, treatment prevented death of CM and the mice died later of anemia. Postponing the severe clinical symptoms is also beneficial in cases of human malaria, giving more time for an appropriate diagnosis and treatment before severe symptoms appear. The method presented here may also be useful for combination therapy of anti-plasmodial and immunomodulatory drugs.